Quadriceps Tendon Rupture in an Adolescent Athlete - William A. Zuke; Beatrice Go; Alexander E. Weber; Brian Forsythe (Case Reports in Orthopedics)
Quadriceps tendon rupture is an uncommon injury that usually occurs in middle-aged and elderly men with a history of chronic illnesses. We report the case of a 17-year-old healthy adolescent male baseball player who sustained this injury as a result of sudden deceleration in his left knee. He initially reported to the emergency department and then presented to our practice, where he was diagnosed with a quadriceps tendon tear. Preoperatively, he was unable to perform a single straight-leg raise. During surgical repair, the free edge of the quadriceps tendon was mobilized and anchored into the superior pole of the patella, followed by sutures to ensure reinforcement of the quadriceps footprint. His postoperative course progressed normally, demonstrating full range of motion at 3 months and return to team training at 5 months. Unlike previously reported quadriceps tendon ruptures in adolescents, to our knowledge, this is the first report of a patient who sustained such an injury without previous trauma to his knee or quadriceps mechanism. It is possible that weakened tendon integrity from repeated microtrauma during training combined with the sudden weight change distribution may have resulted in the injury. As urgent surgical intervention is necessary to ensure efficient recovery and return to sport, the sports medicine practitioner must remain educated and vigilant on caring for these patients.